2015
DOI: 10.1021/acs.orglett.5b02463
|View full text |Cite
|
Sign up to set email alerts
|

Trialkyl Methanetricarboxylate as Dialkyl Malonate Surrogate in Copper-Catalyzed Enantioselective Propargylic Substitution

Abstract: The first copper-catalyzed enantioselective propargylation of trialkyl methantricarboxylate with propargylic alcohol derivatives was developed. The tricarboxylate unit in the obtained adducts could be easily transformed into a malonate moiety by treating with in situ generated NaOEt in excellent yield without racemization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 36 publications
(28 reference statements)
1
11
1
Order By: Relevance
“…Figure 1 b indicates that electron-rich phosphines are superior to electron-deficient phosphines possibly because electron-rich phosphine can facilitate the cleavage of the propargylic C–O bond when Cu-2 is converted to Cu-3 . Unlike other copper-catalyzed propargylation methods performed in aprotic solvents, 25 29 polydentate ligands did not accelerate the reaction in water in this study. Therefore, the copper-catalyzed propargylic C–O bond cleavage in water requires different ligand design principles.…”
Section: Results and Discussioncontrasting
confidence: 76%
“…Figure 1 b indicates that electron-rich phosphines are superior to electron-deficient phosphines possibly because electron-rich phosphine can facilitate the cleavage of the propargylic C–O bond when Cu-2 is converted to Cu-3 . Unlike other copper-catalyzed propargylation methods performed in aprotic solvents, 25 29 polydentate ligands did not accelerate the reaction in water in this study. Therefore, the copper-catalyzed propargylic C–O bond cleavage in water requires different ligand design principles.…”
Section: Results and Discussioncontrasting
confidence: 76%
“…The success of copper-Pybox complexes for enantioselective propargylic substitution reactions prompted Wu and co-workers in the year 2015 for the rst time developed enantioselective propargylation of trialkyl methane tricarboxylate 159 with propargylic alcohol derivatives 158, using pybox ligand 160, Scheme 70. 101 The reaction proceeded via the formation of copper allenylidene complexes as key intermediates following the attack of the trialkyl methane tricarboxylate. The temperature shi from room temperature to 0 C drastically improved the enantioselectivity from 31% ee to 68% ee.…”
Section: Copper Derived Catalystsmentioning
confidence: 99%
“…In practice however, it is not clear how rigorously these good‐practice procedures should be implemented. Indeed, in contrast to the benzyl and monoester enolate carbanions involved in the anionic polymerization of styrenes and (meth)acrylates, respectively, CH 2 C(COOR) 2 (−) malonate carbanions do not react with CO 2 under normal conditions, the formed adduct CH 2 C(COOR) 2 COO (−) being thermodynamically unstable . Likewise, proton transfer to water should not thermodynamically occur in solvents such as DMSO (p K a (H 2 O in DMSO) = 31.4, p K a (Et‐CH(COOMe) 2 = 18.5) .…”
Section: Resultsmentioning
confidence: 99%
“…FT purge VN purge Glovebox [19,20] Likewise, proton transfer to water should not thermodynamically occur in solvents such as DMSO (pK a (H 2 O in DMSO) = 31.4, pK a (EtCH(COOMe) 2 = 18.5). [21,22] Con versely, authors have indicated that malonate carbanions highly diluted in DMSO disappear over time at room tem perature, although the nature of the reaction has never been established.…”
Section: Design Of a Minimal Set Of Polymerization Conditionsmentioning
confidence: 99%